2006
DOI: 10.1161/circulationaha.106.639450
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Implantation of the CoreValve Self-Expanding Valve Prosthesis in High-Risk Patients With Aortic Valve Disease

Abstract: Background— The morbidity and mortality of surgical aortic valve replacement are increased in elderly patients with multiple high-risk comorbid conditions. Therefore, a prospective, single-center, nonrandomized study was performed in high-risk patients with aortic valve disease to evaluate the feasibility and safety of percutaneous implantation of a novel self-expanding aortic valve bioprosthesis (CoreValve). Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
350
1
38

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 641 publications
(397 citation statements)
references
References 22 publications
8
350
1
38
Order By: Relevance
“…Atualmente cerca de 25 mil pacientes já foram tratados com esse dispositivo no mundo e a experiência acumulada com o emprego dessas biopróteses em pacientes com contraindicação ou com alto risco cirúrgico indica que os resultados são bastante promissores. [7][8][9][10][11][12] Recentemente, iniciou-se a experiência com o sistema CoreValve TM no Brasil, 13,14 que motivou a criação de um registro nacional para aferir os resultados do implante percutâneo de biopróteses aórticas em nosso meio.…”
Section: Key-wordsunclassified
“…Atualmente cerca de 25 mil pacientes já foram tratados com esse dispositivo no mundo e a experiência acumulada com o emprego dessas biopróteses em pacientes com contraindicação ou com alto risco cirúrgico indica que os resultados são bastante promissores. [7][8][9][10][11][12] Recentemente, iniciou-se a experiência com o sistema CoreValve TM no Brasil, 13,14 que motivou a criação de um registro nacional para aferir os resultados do implante percutâneo de biopróteses aórticas em nosso meio.…”
Section: Key-wordsunclassified
“…The anesthetic technique remains uncertain, as there are schools using the deep sedation technique, others using general anesthesia, and still another school using combined epidural anesthesia with sedation 4,[12][13][14][15][16] . General anesthesia and deep sedation have been used in several studies with good results 4,10,[16][17][18][19][20][21][22][23][24][25][26][27] . In our case series, we used general anesthesia due to the need for prolonged immobilization of patients in uncomfortable tables, tendency for hypothermia, the team's learning curve, need for surgical repair of catheterized arteries, TEE use, possibility of neurological complications and surgical intervention with cardiopulmonary bypass (CPB), and little knowledge on the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several clinical trials with different devices have been reported 4 . There are currently two types of prostheses for clinical use: CoreValve (Medtronic Inc., Minneapolis, MN) and Edwards-Sapien (Edwards Life Sciences Inc., Irvine, CA) 3,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…A self-expanding prosthetic valve can be deployed percutaneously via a retrograde approach in approximately 84-93% of patients. When successfully implanted, it increases aortic valve area, reduces transvalvular gradients, and improves New York Heart Association functional class, but major adverse cardiac events occurred in as many as 32% of patients at short term follow-up, which included death in 20% [10][11][12]. The largest trial to date which included 86 patients reported a procedural mortality of 6%, a 30-day mortality of 12%, and a cumulative incidence of death, stroke, and myocardial infarction of 22% [12].…”
Section: Discussionmentioning
confidence: 99%